Kepemilikan Rumah Susun Di Indonesia - R. Suharto; Siti Malikhatun Badriyah; Kashadi Kashadi (Faculty of Law, Diponegoro University, 2019)
Technologically, a multi-storey building system whose spaces can be used individually has long been known in Indonesia. The system of building ownership is a single ownership system that is now being developed which is ownership of a multi-storey building with shared property, which is called rumah susun, condominium, or strata title. Ownership of Satuan Rumah Susun (HMSRS) is a new institution of material rights, this HMSRS is individual and separate, in addition to ownership of the apartment unit the ownership rights to the apartment unit (HMSRS) concerned also include joint ownership of what is called a joint part, shared objects, and shared land where all are inseparable from the SRS concerned.ABSTRAKSecara teknologi, sistem Gedung bertingkat yang ruang-ruangnya dapat dipakai secara individu sudah lama dikenal di Indonesia. Sistem pemilikan Gedung tersebut adalah sistem pemilikan tunggal yang sekarang dikembangkan adalah kepemilikan Gedung bertingkat dengan milik bersama, yang disebut dengan rumah susun, kondominium, atau strata title. Hak Milik Satuan Rumah Susun (HMSRS) merupakan suatu Lembaga baru hak kebendaan, HMSRS ini bersifat perorangan dan terpisah, selain pemilikan atas satuan rumah susun hak pemilikan atas satuan rumah susun (HMSRS) yang bersangkutan meliputi juga kepemilikan bersama atas apa yang disebut bagian bersama, benda bersama, dan tanah bersama di mana semuanya merupakan suatu kesatuan yang tidak terpisahkan dengan SRS yang bersangkutan.